2015
DOI: 10.1002/ange.201410757
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple Switching of Pleated Foldamers of Tetrathiafulvalene–Bipyridinium Alternating Dynamic Covalent Polymers

Abstract: Tw od ynamic covalent polymers P1 and P2 were prepared by alternately linking electron-richtetrathiafulvalene (TTF) and electron-deficient bipyridinium (BIPY 2+ )t hrough hydrazone bonds.Inacetonitrile,the polymers were induced by intramolecular donor-acceptor interactions to form pleated foldamers,which unfolded upon oxidation of the TTF units to the radical cation TTFC + .R eduction of the BIPY 2+ units to BIPYC + led to the formation of another kind of pleated secondary structures,w hicha re stabilized by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…This redox-controlled actuating behavior, which has also been observed in polypyrrole 63 , 64 and polyaniline-based 65 systems—where radical chemistry also plays an important role in governing their properties—makes it possible for these viologen-based foldamers to be incorporated into polymeric materials to serve as fast-response actuators. Moreover, Li et al 66 have reported polymers whose structures are composed of alternating TTF and BIPY 2+ units. By switching on and off the radical-pairing interactions between BIPY •+ units through redox chemistry, these polymers can change their folding conformations reversibly between two states.…”
Section: Multistimulus-responsive Materialsmentioning
confidence: 99%
“…This redox-controlled actuating behavior, which has also been observed in polypyrrole 63 , 64 and polyaniline-based 65 systems—where radical chemistry also plays an important role in governing their properties—makes it possible for these viologen-based foldamers to be incorporated into polymeric materials to serve as fast-response actuators. Moreover, Li et al 66 have reported polymers whose structures are composed of alternating TTF and BIPY 2+ units. By switching on and off the radical-pairing interactions between BIPY •+ units through redox chemistry, these polymers can change their folding conformations reversibly between two states.…”
Section: Multistimulus-responsive Materialsmentioning
confidence: 99%